2011
DOI: 10.1002/btpr.645
|View full text |Cite
|
Sign up to set email alerts
|

Dual salt precipitation for the recovery of a recombinant protein from Escherichia coli

Abstract: When considering worldwide demand for biopharmaceuticals, it becomes necessary to consider alternative process strategies to improve the economics of manufacturing such molecules. To address this issue, the current study investigates precipitation to selectively isolate the product or remove contaminants and thus assist the initial purification of a intracellular protein. The hypothesis tested was that the combination of two or more precipitating agents will alter the solubility profile of the product through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…The suitability grades for pretreatment and cell harvesting technologies are the same while there are some variations for cell disruption and phase isolation options. HPH (high pressure homogenization) could be a good choice as it has been used previously for IN-SOL products (Balasundaram et al, 2011). Soluble products are more susceptible to chemical interactions by acids and alkalis, hence chemical lysis may not be suitable in many cases.…”
Section: Intracellular and Soluble Productmentioning
confidence: 99%
“…The suitability grades for pretreatment and cell harvesting technologies are the same while there are some variations for cell disruption and phase isolation options. HPH (high pressure homogenization) could be a good choice as it has been used previously for IN-SOL products (Balasundaram et al, 2011). Soluble products are more susceptible to chemical interactions by acids and alkalis, hence chemical lysis may not be suitable in many cases.…”
Section: Intracellular and Soluble Productmentioning
confidence: 99%
“…Solubility screening with precipitation was evaluated by several groups (Ahmad and Dalby, ; Kramarczyk et al, ; Nfor et al, ; Wiendahl et al, ; Yoshimoto et al, ). More recently, reports have aimed at optimizing precipitation and flocculation conditions for the recovery of mAbs and Fc‐fusion proteins (Balasundaram et al, ; Knevelman et al, ; Ma et al, ; Sheth et al, ). These studies employed a broad range of precipitation agents and conditions to identify regions of superior yield, quality, and impurity clearance.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of high throughput process development (HTPD) has created opportunities for streamlining purification development of biological candidates (Titchener‐Hooker et al, ). Much progress has been made in designing high throughput methods for the purification optimization of a single protein with microfiltration, disruption, extraction, solubilization, refolding, centrifugation, precipitation, filtration, and chromatography (Aucamp et al, ; Balasundaram et al, ; Chhatre and Titchener‐Hooker, ; Coffman et al, ; Kong et al, ; Peng et al, ; Tait et al, ; Treier et al, ; Tustian et al, ; Walther et al, ; Wenger et al, , ). Many authors have shown how data attained with HTPD can be used to predict performance at much larger scales.…”
Section: Introductionmentioning
confidence: 99%